The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/s41551-016-0015
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell culture: Simply derived epicardial cells

Abstract: A chemically defined protocol requiring no animal-derived components allows for the easier derivation and enduring expansion of epicardial cells from human pluripotent stem cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…While human iPSCs are known to have only partial XaXa (Barakat et al., 2015, Kim et al., 2014), we identified two loci (chrXp11 and chrXp22) encoding genes whose expression levels are associated with two distinct cardiac differentiation trajectories (CMs versus EPDCs). The higher expression of chrXp11 genes in CM-fated iPSCs may at least in part be due to fact that ELK1 and PORCN are both encoded in this interval, as the protein product of PORCN (Porcupine) is inhibited by IWP-2 during CM differentiation (Mo et al., 2013) but not during EPDC differentiation (Bao et al., 2016, Iyer et al., 2015, Witty et al., 2014) (some EPDC protocols inhibit Porcupine but then reactivate the WNT pathway at a later time point [Guadix et al., 2017, Paik and Wu, 2017, Zhao et al., 2017]). Furthermore, we found that ELK1 targets are overexpressed in CM-fated iPSCs, which is consistent with previous studies showing that knockdown of ELK1 in immortalized human bronchial epithelial cells, small airway epithelial cells, and luminal breast cancer cell line (MCF-7) is associated with increased EMT (Desai et al., 2017, Tatler et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…While human iPSCs are known to have only partial XaXa (Barakat et al., 2015, Kim et al., 2014), we identified two loci (chrXp11 and chrXp22) encoding genes whose expression levels are associated with two distinct cardiac differentiation trajectories (CMs versus EPDCs). The higher expression of chrXp11 genes in CM-fated iPSCs may at least in part be due to fact that ELK1 and PORCN are both encoded in this interval, as the protein product of PORCN (Porcupine) is inhibited by IWP-2 during CM differentiation (Mo et al., 2013) but not during EPDC differentiation (Bao et al., 2016, Iyer et al., 2015, Witty et al., 2014) (some EPDC protocols inhibit Porcupine but then reactivate the WNT pathway at a later time point [Guadix et al., 2017, Paik and Wu, 2017, Zhao et al., 2017]). Furthermore, we found that ELK1 targets are overexpressed in CM-fated iPSCs, which is consistent with previous studies showing that knockdown of ELK1 in immortalized human bronchial epithelial cells, small airway epithelial cells, and luminal breast cancer cell line (MCF-7) is associated with increased EMT (Desai et al., 2017, Tatler et al., 2016).…”
Section: Discussionmentioning
confidence: 99%